Karcinom nosnega žrela - Strojan, Primož (Medicinski razgledi, 2004)
Nasopharyngeal carcinoma is as rare in Slovenia as in other Western countries.Given the etiopathogenetic interdependence of viral infection, neoplastic transformation and host immune response, nasopharyngeal carcinoma is a unique tumor model which can be studied from different perspectives. The complexity of nasopharyngeal anatomy and relationships of the nasopharynx to adjacent tissues has a decisive role in specifying treatment possibilities, exposing radiotherapy as a key treatment modality. The results of most recent retrospective and prospective randomized studies show that radiotherapy is successfully supplemented with chemotherapy. A routine use of new advances in technology, including computer tomography and magnetic resonance imaging, unified histology grading system and TNM staging system of the nasopharyngeal carcinoma, and improved treatment planning and execution of radiotherapy have yielded significantly better treatment results. Additional treatment of local,regional or systemic recurrences after completed initial treatment may be curative in a considerable proportion of patients.
Keywords: Nasopharyngeal Neoplasms; Nazofaringealne novotvorbe; Etiology; žrelo; Diagnosis; nosno žrelo; rak (medicina); Therapy; zdravljenje; diagnostika